PET–CT of mesenteric panniculitis: A potential confounder of lymphoma. Issue 1 (February 2015) - Sideras, Panagiotis A.; Patil, Vivek; Li, Zhonghua; Heiba, Sherif; Kostakoglou, Lale
Abstract Mesenteric panniculitis is an inflammatory condition involving the adipose tissue of the mesentery. Historically, this entity has been described with several names. Histologically, it can be categorized further according to pathological changes of chronic inflammation, fat necrosis and fibrosis. Mesenteric panniculitis was rarely diagnosed before the era of ultrasound and CT. With more modern imaging modalities such as 2-fluoro-18-deoxyglucose-Positron Emission Tomography/Computed Tomography (FDG-PET/CT), increased metabolism is expected due to its inflammatory component. This in turn can create potential pitfalls especially when restaging patients after treatment with co-existing lymphomas. Here, we will discuss the case of a patient with mesenteric panniculitis and coexisting lymphoma.